To negotiate, mediate or litigate? Examining the durability of divorce outcomes in the Singapore family courts. (26th June 2022) - Quek Anderson, Dorcas; Chua, Eunice; Ning, Yilin
Abstract: For many years, the courts have been grappling with the paradox of marriages—the most intimate of relationships—being dissolved in the courts that represent a public and adversarial setting. Despite the growth of divorce interventions, the perennial struggle remains in many courts on how to reduce the intense acrimony of divorce litigation. The question remains on the scope of "mainstream" interventions to be offered by the courts to divorce litigants. The current study therefore explores the use of court‐connected negotiation, mediation, and litigation in the Singapore Family Justice Courts. It uses a statistical method of survival analysis to produce insights on re‐litigation trends over time and to predict the future risk of re‐litigation. Mediated divorces were found to have consistently higher durability than litigated cases and negotiated settlements. Negotiated divorce outcomes had the worst durability when the survival analysis was done in relation to re‐litigation caused by extraneous factors. These findings strongly suggest that mediation should be a highly recommended mode of dispute resolution for divorcing parties, especially when there are children to the marriage, and that there are benefits of having a neutral third party to help the parties reach a sustainable settlement. Key Points for the Family Court Community: This study showed that mediated divorce cases were more durable than litigated and negotiated cases amongst cases with children. The higher durability for mediated cases appeared to take effect in the long‐term, after 1 year has lapsed since the divorce order. The higher durability for mediated cases with children appeared to validate the courts' policy of adopting a multi‐disciplinary approach involving mediation being conducted by judges, volunteer mediators and social science experts. The higher durability of mediated cases with children was seen when examining variations linked to the parties' lack of cooperation as well as variations linked to other reasons. This suggests that the mediation process not only has a favourable impact on the parties' post‐divorce ability to manage disputes, but also contributes to developing sustainable settlements. The presence of legal advice did not make a difference to the above findings, suggesting that the presence of a neutral third party—a judge or a mediator—could result in more sustainable divorce outcomes. Negotiated divorce outcomes were the least durable when durability analysis was done in relation to variations sought due to extraneous circumstances such as errors and implementation issues. This findings suggests that negotiated settlements are less sustainable than litigated and mediated divorce outcomes. While amicably negotiated settlements are to be encouraged, it is critical that the settlements are arrived through the parties' informed consent and with understanding of the salient issues.